2021
DOI: 10.1063/5.0037864
|View full text |Cite
|
Sign up to set email alerts
|

Single vs double anti-crossing in the strong coupling between surface plasmons and molecular excitons

Abstract: Strong coupling between surface plasmons and molecular excitons may lead to the formation of new hybrid states—polaritons—that are part light and part matter in character. A key signature of this strong coupling is an anti-crossing of the exciton and surface plasmon modes on a dispersion diagram. In a recent report on strong coupling between the plasmon modes of a small silver nano-rod and a molecular dye, it was shown that when the oscillator strength of the exciton is large enough, an additional anti-crossin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In most studies of strong coupling with ENZ materials, ENZ modes are involved. ,, ENZ modes are surface modes that occur in deep-subwavelength films; such surface modes can only couple to p -polarized light with momentum greater than that of free-space light. , Within the radiative region, thin ENZ films can also support Berreman modes. Berreman modes provide strong out-of-plane electric-field enhancement due to the continuity of the normal component of D⃗ = ε E⃗ ; therefore, the excitation of Berreman modes also requires TM-polarized light. Longitudinal resonances can exist around the ENZ point of a material with low loss . The longitudinal resonance arises due to the presence of surface charge, which also requires electric field normal to the surface to excite it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies of strong coupling with ENZ materials, ENZ modes are involved. ,, ENZ modes are surface modes that occur in deep-subwavelength films; such surface modes can only couple to p -polarized light with momentum greater than that of free-space light. , Within the radiative region, thin ENZ films can also support Berreman modes. Berreman modes provide strong out-of-plane electric-field enhancement due to the continuity of the normal component of D⃗ = ε E⃗ ; therefore, the excitation of Berreman modes also requires TM-polarized light. Longitudinal resonances can exist around the ENZ point of a material with low loss . The longitudinal resonance arises due to the presence of surface charge, which also requires electric field normal to the surface to excite it.…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal resonances can exist around the ENZ point of a material with low loss. 32 The longitudinal resonance arises due to the presence of surface charge, which also requires electric field normal to the surface to excite it. Furthermore, Ag possesses a second ENZ point at 4.6 eV, at which no anticrossing or absorption is observed.…”
Section: Resultsmentioning
confidence: 99%
“…These planar nanoscopic thin-film stacks are versatile since one can study the associated observables of the modes when one: (i) varies two independent variables, the in-plane wave vector k ρ /k 0 and the frequency ω, (ii) modifies the nature of the material constituents and the thin-film stack thicknesses. The resonant phenomena present in these MIM thin film stacks, due to the interaction between SPP and PWG modes giving rise to avoided crossings, have been discussed in several review papers by Barnes et al [3][4][5], Achlan [6] and Raseev and Achlan [7]. Miroshnichenko et al [8] and Luk'yanchuk et al [9] have discussed these thin film stacks and nanostructures identifying Fano resonance shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The resonant angle must be smaller than 90 • , thus the thickness of CsPbBr 3 layer must be smaller than 29 nm and the corresponding Rabi energy is about 90 meV. Theoretical studies of Rabi energy in Krestchmann configuration have been reported previously [20,22,27]. Pang has revealed that the Rabi energy will increase with the increment of the thickness of the Ag layer [22].…”
mentioning
confidence: 99%
“…In their work, the increment of Ag layer thickness will not cause the shift of E SP (θ), thus the resonant condition will be always fulfilled. Tan has discussed the influence of the oscillator strength on the Rabi splitting [27]. They concluded that with large oscillator strength, a new mode emerges and induces a double anticrossing structure.…”
mentioning
confidence: 99%